Radiation Treatment of Foods: I. Radurization of Fresh Eviscerated Poultry - Idziak, Edmund S. (1968)
Radurization processing of fresh eviscerated poultry has been microbiologically studied. The recommended dose of 0.5 Mrads extended the shelf life at 5 C by approximately 14 days. This treatment also effected a 10 and 11 log reduction in the number of viable Salmonella species and Staphylococcus aureus strains, respectively. Recycling these organisms at sublethal doses of irradiation resulted in strains possessing increased irradiation resistance. Shifts in the microbial ecology after irradiation and storage resulted, in some instances, in the isolation of organisms tentatively identified as Moraxella sp. and Herellea vaginicola.